ANALISIS PENGARUH REPUTASI KAP, AUDIT TENURE, KOMISARIS INDEPENDEN, KOMITE AUDIT DAN UKURAN PERUSAHAAN TERHADAP AUDIT REPORT LAG (Studi Empiris Pada Perusahaan Sektor Teknologi yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024) - Fadillah Mohammad Rafid; Agus Purwanto (Diponegoro Journal of Accounting, 2026)
This research aims to analyze and provide empirical evidence regarding the effect of public accounting firm reputation, audit tenure, the proportion of independent commissioners, the educational background of audit committee members, and firm size on audit report lag. The research utilizes secondary data obtained from financial statements, independent auditor reports, and annual reports published on the official website of the Indonesia Stock Exchange (www.idx.co.id). The population of this study consists of 47 technology companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Using a purposive sampling method, 31 companies were selected as the research sample. The analytical method employed in this study is multiple linear regression analysis to examine the extent to which the independent variables public accounting firm reputation, audit tenure, proportion of independent commissioners, educational background of audit committee members, and firm size affect audit report lag. The results indicate that audit tenure has a significant influence on audit report lag, whereas public accounting firm reputation, the proportion of independent commissioners, the educational background of audit committee members, and firm size do not have a significant effect.